Coding and Non-coding RNAs: Molecular Basis of Forest-Insect Outbreaks - Zhang, Sufang; Shen, Sifan; Yang, Zhongwu; Kong, Xiangbo; Liu, Fu; Zhen, Zhang (Frontiers in Cell and Developmental Biology, 2020)
Insect population dynamics are closely related to ‘human’ ecological and economic environments, and a central focus of research is outbreaks. However, the lack of molecular-based investigations restricts our understanding of the intrinsic mechanisms responsible for insect outbreaks. In this context, the moth Dendrolimus punctatus Walker can serve as an ideal model species for insect population dynamics research because it undergoes periodic outbreaks. Here, high-throughput whole-transcriptome sequencing was performed using D. punctatus sampled during latent and outbreak periods, to systemically explore the molecular basis of insect outbreaks and to identify the involved noncoding RNA (ncRNA) regulators, namely microRNAs, long non-coding RNAs, and circular RNAs. Differentially expressed mRNAs of D. punctatus from different outbreak periods were involved in developmental, reproductive, immune, and chemosensory processes, results that were consistent with the physiological differences in D. punctatus during differing outbreak periods. Targets analysis of the noncoding RNAs indicated that long non-coding RNAs could be the primary ncRNA regulators of D. punctatus outbreaks, while circular RNAs mainly regulated synapses and cell junctions. The target genes of differentially expressed microRNAs mainly regulated the metabolic and reproductive pathways during the D. punctatus outbreaks. Developmental, multi-organismal, and reproductive processes, as well as biological adhesion, characterized the competing endogenous RNA network. Chemosensory and immune genes closely related to the outbreak of D. punctatus were further analyzed in detail: from their ncRNA regulators’ analysis, we deduce that both lncRNA and miRNA may play significant roles. This is the first report to examine the molecular basis of coding and noncoding RNAs’ roles in insect outbreaks. The results provide potential biomarkers for control targets in forest insect management, as well as fresh insights into underlying outbreak-related mechanisms, which could be used for improving insect control strategies in the future.